3(y+9)=12y+133

Simple and best practice solution for 3(y+9)=12y+133 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 3(y+9)=12y+133 equation:



3(y+9)=12y+133
We move all terms to the left:
3(y+9)-(12y+133)=0
We multiply parentheses
3y-(12y+133)+27=0
We get rid of parentheses
3y-12y-133+27=0
We add all the numbers together, and all the variables
-9y-106=0
We move all terms containing y to the left, all other terms to the right
-9y=106
y=106/-9
y=-11+7/9

See similar equations:

| x-4=0.7 | | 14c=4 | | k(k-2)=5 | | 6=20+x/2 | | 10x+2-8x+3=8x+1-x+8 | | -6x-2x=9 | | -19-×=5x+23 | | 1000=180+2.5x | | 2/3w-5=5/3w | | (2x+4)/3=x/6-3 | | -6x-6=10-4x | | 2/9-5x=-268/9 | | 5c-6=6-3. | | 2.3x-9.96=4.3 | | 9x+2=42 | | 5x2-56x-16=0 | | 5c-4=6-3c | | (x^2+4)^2=0 | | 99=2/3x-5 | | n^=5n-6 | | (x-5)^2=-3 | | 6(1-r)=31-r | | 20=15.04x+4.9x^2 | | 1/4=x+3/4 | | F(x)=x4+5x | | 6x10=3 | | 0=1/6×y+8 | | 4x−5=2+3(x−3) | | 3y-30=2y+42 | | 4p^2-13p+9=0 | | -5x-39=6x+27 | | -5x+9+4=9 |

Equations solver categories